Estudo comparativo dos ensaios de CBR e Mini-CBR para solos de Uberlândia-MG - Souza, Ricardo Andrade de (2007)
This present work shows a comparative study between the tests of CBR and the tests of Mini-CBR to the soils of Uberlândia - MG, aiming at to extend the use of the Mini-CBR, in view of its advantages in relation to the CBR. The main advantages of the test of Mini-CBR are more practical, demands a smaller amount of samples, it has a faster execution procedure, demands less physical effort and reduces the operator s influence, furthermore, it is less expensive than the CBR test. This study researched the existence of a correlation between values of CBR and Mini-CBR for the Uberlândia soils, and/or to validate the correlations already existing proposal by others writers. They were studied samples of 8 types of soils of the Uberlândia s city studied by Andrade (2005). The samples were compacted in 5 different moisture contents necessaries to the definition of the compaction curve. Therefore, for each sample of soil they were performed the traditional characterization tests, Mini-CBR tests and loss of weight by immersion, for MCT classification, CBR in the normal energy test, Mini-CBR - without immersion/without overload, Mini-CBR - with immersion/with overload and Mini-CBR - without immersion/without overload with the soil compacted in a only face of the specimen. For the analyzed soils, the tests results had shown that there is no clear relation between the values of CBR and Mini-CBR, independent of the types of soils (origin), of the MCT classification and the test procedures. With relation the maximum dry density and optimum moisture content in the energy of the ordinary compaction test, in the interval of water contents of +/- 2% for the sands and +/- 4% for clays, it there is an excellent relation between the values obtained through compaction in miniature and the ordinary compaction test, independent of compaction mould be large or small.